2022
DOI: 10.1002/tcr.202200222
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Based Metallenes for Fuel Cell Reactions

Abstract: Pd-based metallenes, atomically thin layers composed primarily of under-coordinated Pd atoms, have emerged as the newest members in the family of two-dimensional (2D) nanomaterials. Moreover, the unique physiochemical properties, high intrinsic activity associated with metallenes coupled with the ease of applying chemical modifications result in great potential in catalyst engineering for fuel cell reactions. Especially in recent years, interest in Pd-based metallenes is growing, as evidenced by surge in avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 119 publications
0
11
0
Order By: Relevance
“…Alloying noble metals with other non-noble metals is widely considered as a promising strategy for modifying the electronic structure of catalysts to optimize the binding strength with intermediates. [35][36][37][38] Pd metallenes have been firstly developed for boosting electrocatalytic reactions. However, systematical electrochemical measurements and theoretical analyses have uncovered that the intrinsic electronic structure of Pd is unfavorable for the electrocatalytic oxygen reduction reaction (ORR), which thus calls for the development of effective modification strategies.…”
Section: Alloyingmentioning
confidence: 99%
“…Alloying noble metals with other non-noble metals is widely considered as a promising strategy for modifying the electronic structure of catalysts to optimize the binding strength with intermediates. [35][36][37][38] Pd metallenes have been firstly developed for boosting electrocatalytic reactions. However, systematical electrochemical measurements and theoretical analyses have uncovered that the intrinsic electronic structure of Pd is unfavorable for the electrocatalytic oxygen reduction reaction (ORR), which thus calls for the development of effective modification strategies.…”
Section: Alloyingmentioning
confidence: 99%
“…In addition to the synthesis of 2D hexagonal nanoplates, 2D Pd-based metallenes are also reported to be promising candidates for driving the ORR. [109][110][111][112][113][114][115][116][117] Luo et al demonstrated that PdMo metallenes can exhibit outstanding electrocatalytic ORR performance (Fig. 11a-c).…”
Section: D Pd-based Nanostructuresmentioning
confidence: 99%
“…[8][9][10] However, with sluggish kinetics due to the multistep proton-coupled electron transfer, the anode oxygen evolution reaction (OER) of water electrolysis significantly limits the hydrogen production efficiency and rate. 11,12 To improve the OER kinetics and accelerate the reaction rate, introducing appropriate electrocatalysts is a practicable approach. For anodic OER, the state-of-the-art electrocatalysts are Ir/Ru oxides, but their rarity and high costs cannot satisfy scaled-up application yet.…”
Section: Introductionmentioning
confidence: 99%